2023
DOI: 10.1186/s12935-023-03147-7
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging a disulfidptosis‑related lncRNAs signature for predicting the prognosis and immunotherapy of glioma

Di Chen,
Qiaoqiao Li,
Yuan Xu
et al.

Abstract: Background Gliomas, a prevalent form of primary brain tumors, are linked with a high mortality rate and unfavorable prognoses. Disulfidptosis, an innovative form of programmed cell death, has received scant attention concerning disulfidptosis-related lncRNAs (DRLs). The objective of this investigation was to ascertain a prognostic signature utilizing DRLs to forecast the prognosis and treatment targets of glioma patients. Methods RNA-seq data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…LncRNAs undertake a critical part in modulating malignant behaviors of tumors and have been deemed as possible tumortargets in recent years 43 . DRLs signatures have been reported to forecast survival in various cancers, including www.nature.com/scientificreports/ colon adenocarcinoma 44 , hepatocellular carcinoma 45 , and glioma 46 . Hitherto, there are limited studies on survival significance between DRLs and HPV-negative OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs undertake a critical part in modulating malignant behaviors of tumors and have been deemed as possible tumortargets in recent years 43 . DRLs signatures have been reported to forecast survival in various cancers, including www.nature.com/scientificreports/ colon adenocarcinoma 44 , hepatocellular carcinoma 45 , and glioma 46 . Hitherto, there are limited studies on survival significance between DRLs and HPV-negative OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 374 patients with HCC and 50 healthy individuals were included in subsequent analyses (last accessed: 6 May 2023). Ten disulfidptosis-related genes (GYS1, LRPPRC, NCKAP1, NDUFA11, NDUFS1, NUBPL, OXSM, RPN1, SLC3A2, and SLC7A11) were collected based on previously published studies [ 8 11 , 16 ]. We performed Pearson correlation analysis with a threshold of Pearson’s R > 0.4 and p < 0.001 to assess the relationship between disulfidptosis-related genes and lncRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Liu et al demonstrated that susceptibility of the actin cytoskeleton to disulfide stress leads to disulfidoptosis, proposing a therapeutic avenue targeting disulfidoptosis for cancer treatment [ 8 , 10 ]. Chen et al constructed a disulfidptosis-related lncRNAs signature for predicting the prognosis and immunotherapy of glioma [ 11 ]. However, novel biomarkers linked to disulfidoptosis for HCC prognosis and therapy remain elusive.…”
Section: Introductionmentioning
confidence: 99%